Zombie Papers: A threat to science - Shah, Jenifei; Shah, Jesifei; Subedi, Dharma; Regmi, Prabodh; Thapa, Muna Mharjan; Thapa, Niresh; Shah, Jay N (Journal of Karnali Academy of Health Sciences, 2022)
Zombies are the walking dead. In scientific literature, the Zombie Papers continue to exist and do not die even after the retraction which in itself is a slow process, inconsistent, and inadequate. The top-level evidence and practice guidelines based upon systematic review and meta-analysis get contaminated by the false data from paper mills and Zombie Papers. Science relies on trust. The research and publication of evidence must be ethical and trustworthy. The research publication is a transnational process. It requires the collaboration of stakeholders including readers, editors, institutions, and society beyond the national boundaries. Awareness of Zombie Papers and misconduct is necessary to maintain the integrity of science.